2021
DOI: 10.1186/s12913-021-06756-y
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and opinions of Oral healthcare professionals on screening for Type-2 diabetes

Abstract: Background As part of a larger study on the identification of undiagnosed Type 2 diabetes (T2D), and prediabetes patients in dental settings, this study explored oral healthcare professionals’ (OHP) attitudes with respect to the relevance and appropriateness of screening for prediabetes/T2D in general oral healthcare settings. It also aims to gain a deeper understanding of OHPs’ concerns and perceived barriers to screening for T2D. Methods Semi-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…This limits considerably the effectiveness of diabetes screenings. In other studies the percentage of patients attending GPs following a diabetes risk assessment in the oral healthcare setting (private, public and University clinic) has varied from 20 to 84% [ 4 , 19 , 27 , 33 ]. In each of these studies patients had consented to undertake screening and had been advised of the possibility of being referred to a GP for follow-up and yet subsequent follow-up was low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This limits considerably the effectiveness of diabetes screenings. In other studies the percentage of patients attending GPs following a diabetes risk assessment in the oral healthcare setting (private, public and University clinic) has varied from 20 to 84% [ 4 , 19 , 27 , 33 ]. In each of these studies patients had consented to undertake screening and had been advised of the possibility of being referred to a GP for follow-up and yet subsequent follow-up was low.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to patients attending follow-up appointments with GPs included misplacing the referral letter, being too busy, being away, the perception the condition was not ‘serious enough’ GP’s [ 27 ] lack of knowledge about diabetes, not understanding the importance of follow-up, cost, fear and denial [ 37 ]. Patients not seeking a medical diagnosis was a barrier to the completion of our screening protocol, and further research is needed to understand the reasons for this and develop strategies to overcome it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a current lack of collaboration remains between medical and oral health practitioners to manage these diseases, including screening [ 12 , 13 ]. One study indicated that rural general medical practitioners (GPs) in Australia had concerns about their competence to deal with oral health issues when consulting patients with emergency dental problems.…”
Section: Introductionmentioning
confidence: 99%
“…Standard practice involved providing short-term pain relief, prescriptions for antibiotics, and recommending patients to see an oral health professional [ 14 ]. Another paper looked at barriers within screening in a general practice environment, included legal and reimbursement issues [ 13 ]. This is consistent with general medical practice activity data that show that while GP consultations regularly involve patients raising dental concerns, the GPs’ oral health training and awareness are inadequate to deal with complex oral health issues [ 15 ].…”
Section: Introductionmentioning
confidence: 99%